Parvalbumin tunes spike‐timing and efferent short‐term plasticity in striatal fast spiking interneurons. (30th April 2013) - Orduz, David; Bischop, Don Patrick; Schwaller, Beat; Schiffmann, Serge N.; Gall, David
Key points Fast spiking interneurons (FSIs) modulate output of the striatum and are implicated in severe motor disorders. Selective expression of the calcium‐binding protein parvalbumin (PV) in FSIs raises questions about how PV controls FSI Ca2+ dynamics. Here we report a novel mechanism linking PV‐Ca2+ buffering and FSI spiking as a result of the activation of small conductance (SK) Ca2+‐dependent K+ channels. We also show that, at the presynaptic terminals, PV prevents synaptic facilitation at narrow frequencies at FSI to striatal output neuron synapses. Our data establish that PV is a key element in providing rhythm generation in FSIs as well as filtering striatal output. Thus, FSI neuromodulation via PV and/or SK channels is an interesting target for controlling the establishment of oscillatory frequencies related to the induction or worsening of pathology‐related motor rhythms. Abstract Striatal fast spiking interneurons (FSIs) modulate output of the striatum by synchronizing medium‐sized spiny neurons (MSNs). Recent studies have broadened our understanding of FSIs, showing that they are implicated in severe motor disorders such as parkinsonism, dystonia and Tourette syndrome. FSIs are the only striatal neurons to express the calcium‐binding protein parvalbumin (PV). This selective expression of PV raises questions about the functional role of this Ca2+ buffer in controlling FSI Ca2+ dynamics and, consequently, FSI spiking mode and neurotransmission. To study the functional involvement of FSIs in striatal microcircuit activity and the role of PV in FSI function, we performed perforated patch recordings on enhanced green fluorescent protein‐expressing FSIs in brain slices from control and PV−/− mice. Our results revealed that PV−/− FSIs fired more regularly and were more excitable than control FSIs by a mechanism in which Ca2+ buffering is linked to spiking activity as a result of the activation of small conductance Ca2+‐dependent K+ channels. A modelling approach of striatal FSIs supports our experimental results. Furthermore, PV deletion modified frequency‐specific short‐term plasticity at inhibitory FSI to MSN synapses. Our results therefore reinforce the hypothesis that in FSIs, PV is crucial for fine‐tuning of the temporal responses of the FSI network and for the orchestration of MSN populations. This, in turn, may play a direct role in the generation and pathology‐related worsening of motor rhythms.